Literary Texts of Diverse Ethnicities: Is Translation a Blessing or a Curse? - Shriganeshan, K. (இந்த சமய கலாசார அலுவல்கள ; திணைக்களம், 2021)
Post-colonial literature is a new term for Commonwealth literature which could be divided into two major categories: Literature in English and Literature in other languages. Under Literature in English, there could be two major divisions, namely, English Literature by writers who are native speakers of English and Literature in English by non- native writers. Under the banner Literature in English, there could be two major divisions, namely, those originally written in English and those translated from other languages of diverse ethnicities into English. Critics have spoken of an innovative idiom to express native experience in English but intelligibility is a further problem faced by international readers. Two factors need to be considered. One is that native and traditional metaphors may not be able to express modern life. On the other hand, the range of experiences and problems faced by all natives could not be expressed by the English educated ‘elite’. As found in literary pieces from other commonwealth countries like India and Nigeria, Sri Lankan Tamil poetry in English, too deals with many a theme. The poets have raised their voice on themes like nature, love, nationalism, war, ethnic crisis, terrorism and other problems like unemployment, poverty, alienation, personal grievance, and caste discrimination. There have been tension and differences of opinion among critics and linguists on the use of language, idiom, imagery and the themes used by the writers. The translations of literary texts have created a space for the new generation of readers to realize the plurality and diversity of local traditions. In addition to exposing our culture, traditions and our day to day problems to the international readership, translation has become a medium through which one can understand the life of fellow countrymen speaking a different language. This paper attempts to look into the possibilities of taking it as a blessing to express the voice of the people or a curse to lose the meaning and identity of the very same people.
Keywords: Literature in English; Innovative medium; Meaning; Identity